2010
DOI: 10.1002/ejic.201000430
|View full text |Cite
|
Sign up to set email alerts
|

Shape Evolution and Tunable Properties of Monodisperse Magnetite Crystals Synthesized by a Facile Surfactant‐Free Hydrothermal Method

Abstract: Monodisperse Fe3O4 crystals have been synthesized by a simple hydrothermal method. Reaction conditions are performed in an ethylene glycol (EG)/NaOH system using FeCl3 as the iron source without adding any surfactants. By adjusting the initial molar ratio of NaOH to Fe3+, several morphologies including solid spheres, hollow spheres, spherical chains, tetrakaidecahedrons, octahedrons, and some flowerlike structures can be obtained. Further investigation reveals that all of the spherical structures are formed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Employing various methods, the Fe 3 O 4 with different morphologies have been successfully synthesized, such as spheres [8][9][10][11], octahedrons [12][13][14][15][16][17], cubes [18,7], tetrakaidecahedrons [19], wires [20,21], fractals [22], dendrites [23], hollow structures [24], urchin-like structures [5], nanosheets [1,25], and nanoprisms [26]. However, fine shape control of Fe 3 O 4 microparticles through a simple synthesis process with good size and shape-dependent properties remains a difficult task [27]. Recently, Zhao and co-workers [28] synthesized different morphological single-crystal Fe 3 O 4 by a polyol method in ethylene glycol at 200 • C. Zhang et al [15] prepared different morphological Fe 3 O 4 by a thermal decomposition method using Fe(acac) 3 precursor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Employing various methods, the Fe 3 O 4 with different morphologies have been successfully synthesized, such as spheres [8][9][10][11], octahedrons [12][13][14][15][16][17], cubes [18,7], tetrakaidecahedrons [19], wires [20,21], fractals [22], dendrites [23], hollow structures [24], urchin-like structures [5], nanosheets [1,25], and nanoprisms [26]. However, fine shape control of Fe 3 O 4 microparticles through a simple synthesis process with good size and shape-dependent properties remains a difficult task [27]. Recently, Zhao and co-workers [28] synthesized different morphological single-crystal Fe 3 O 4 by a polyol method in ethylene glycol at 200 • C. Zhang et al [15] prepared different morphological Fe 3 O 4 by a thermal decomposition method using Fe(acac) 3 precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhao and co-workers [28] synthesized different morphological single-crystal Fe 3 O 4 by a polyol method in ethylene glycol at 200 • C. Zhang et al [15] prepared different morphological Fe 3 O 4 by a thermal decomposition method using Fe(acac) 3 precursor. Although well-defined Fe 3 O 4 crystals with different morphologies have been synthesized by relative simple methods [15,[27][28][29], it is still a great challenge to further develop simple and low-cost approaches for the synthesis of homogeneous Fe 3 O 4 microparticles with variable shapes and sizes. To the best of our knowledge, the controlled preparation of Fe 3 O 4 microparticles with adjustable morphologies and sizes by changing the ratio between NaOH and C 2 H 6 O 2 in aqueous solution has not hitherto been reported.…”
Section: Introductionmentioning
confidence: 99%
“…As first sight this last number does not fully agree to those of Chen but a closer look to Figure 1(c) reveals that the features decorating the CNTs' surface are composed of small spherical nanoparticles that are aggregated. Liu et al [24] described such morphology when highly alkaline conditions were used in the synthesis of magnetite nanocrystals with EG, as a consequence of an isotropic growth follow by crystallization. Zhang et al [25] also reported that at higher pH, smaller gold nanoparticles decorated CNTs when using UV as reducing medium.…”
Section: Effect Of Naoh Additionmentioning
confidence: 99%
“…A lot of research papers report that the solvothermal method were often involved into employing some kinds of surface active agents for the sake of controlling morphology. But these agents are usually adsorbed onto the surface of the formed product and are difficult to eliminate, which may deteriorate the properties and limit the applications of the final products [17].…”
Section: Introductionmentioning
confidence: 99%